(untitled) (Journal of Parents and Teachers, 2026)
For some, disciplines are independent tools in which students must first specialise so that they can then use them together to analyse reality. For others, it is the other way around: reality is at the core of the curriculum, and disciplines should not exist as isolated tools, independent of what happens in life. We propose the newspaper as an interdisciplinary model, through the study of news in class. In addition, ten interdisciplinary models are offered, ten ways of finding the relationship between a news item and different disciplines.